On the deviation from Maxwellian of the ion velocity distribution functions in the turbulent magnetosheath. (February 2020) - Perri, S.; Perrone, D.; Yordanova, E.; Sorriso-Valvo, L.; Paterson, W. R.; Gershman, D. J.; Giles, B. L.; Pollock, C. J.; Dorelli, J. C.; Avanov, L. A.; Lavraud, B.; Saito, Y.; et al.
Abstract : The deviation from thermodynamic equilibrium of the ion velocity distribution functions (VDFs), as measured by the Magnetospheric Multiscale (MMS) mission in the Earth's turbulent magnetosheath, is quantitatively investigated. Making use of the unprecedented high-resolution MMS ion data, and together with Vlasov–Maxwell simulations, this analysis aims at investigating the relationship between deviation from Maxwellian equilibrium and typical plasma parameters. Correlations of the non-Maxwellian features with plasma quantities such as electric fields, ion temperature, current density and ion vorticity are found to be similar in magnetosheath data and numerical experiments, with a poor correlation between distortions of ion VDFs and current density, evidence that questions the occurrence of VDF departure from Maxwellian at the current density peaks. Moreover, strong correlation has been observed with the magnitude of the electric field in the turbulent magnetosheath, while a certain degree of correlation has been found in the numerical simulations and during a magnetopause crossing by MMS. This work could help shed light on the influence of electrostatic waves on the distortion of the ion VDFs in space turbulent plasmas.